4D Research and Development Model: Trends, Challenges, and Opportunities Review - Rosita Budi Indaryanti; Harsono Harsono; Sutama Sutama; Budi Murtiyasa; Bambang Soemardjoko (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
The 4D model—Define, Design, Develop, and Disseminate—is a widely recognized framework for research and development (R&D), particularly in educational innovation. This systematic literature review (SLR) examines the implementation trends, challenges, and opportunities of the 4D model across various fields, analyzing 50 peer-reviewed journal articles published between 2013 and 2023 using PRISMA guidelines. Results indicate that the 4D model is predominantly applied in educational contexts, such as curriculum design and instructional material development, with limited adoption in non-educational sectors. Major challenges include a lack of empirical validation and difficulties in adapting the model to multidisciplinary applications. Opportunities for enhancing the 4D model include integration with contemporary methodologies, such as agile approaches and artificial intelligence. This study provides recommendations for future research and practical insights to broaden the applicability and impact of the 4D model.